EFEKTIVITAS TERAPI MELUKIS DAN MENGGAMBAR PADA PASIEN SKIZOFRENIA - Wulan, Winda Ratna (Journal Healthcare Education, 2025)
The World Health Organization states that there are approximately 23 million people with schizophrenia worldwide. The positive and negative symptoms experienced by patients with schizophrenia can significantly affect their ability to engage in activities, build relationships, and live independently. Art therapy, as part of a therapeutic modality, serves as a therapeutic intervention and can be used as a tool to provide psychological insights and promote emotional maturity. Painting or drawing can visualize symbols that emerge from the subconscious as expressions of the patients.The research method involved electronic searches using databases such as PubMed Health, ScienceDirect, and CrossRef, with the keyword "art therapy." The search for journals was further narrowed by adding keywords such as "psychiatric, schizophrenia, drawing, and painting," with a publication range between 2013 and 2018, and utilizing research methods including randomized control trials and quasi-experimental studies. The results of the research indicate that the management of art therapy through painting and drawing in patients with schizophrenia can enhance motivation, improve interpersonal relationships, increase medication adherence, improve sleep patterns, reduce both positive and negative symptoms, and decrease levels of anxiety, depression, and anger. Based on a literature review of four journals, it was found that painting therapy is effective in improving the condition of patients with schizophrenia.